KONDISI KESEHATAN KARANG FUNGIIDAE DI PERAIRAN PULAU PRAMUKA, KEPULAUAN SERIBU - Beginer Subhan; Fadhilah Rahmwawati; Dondy Arafat; Nur Ari Bayu (Jurnal Teknologi Perikanan dan Kelautan, 2011)
This research was done on five sites (that are Southwestward, Marine Protected Area, Northeastward, and pier 1) on Pramuka Island, Seribu Islands, Jakarta. The data was taken by using Belt Transect Method which is unfold type for 60 meters parallels with shoreline, 2 meters in width of visibility, and 5 meters in depth. Kinds of coral that was collected are those from Family of Fungiidae. There are five genera from Family of Fungiidae found in Pramuka Island, that are Heliofungia, Herpolitha, Fungia, Ctenactis, and Sandalolitha. From 106 of total coral’s individu of Fungiidae in all sites of Pramuka Island, as much as 38.68% (41 individuals) of Fungiidae are healthy and as much as 61.32% (65 individuals) is got disease. Fungia is the most affected by coral disease. 19 of 61 individuals of Fungia (31.15%) are still healthy and 42 individuals (68.85%) affected by coral disease. On 24 individuals of Ctenactis that has found in all station, 70.83% of them affected by coral disease. From 13 individuals of Herpolitha, 38,46% of them affected by coral disease and 61,54% is healthy. From 6 individuals of Sandalolitha, as much as 50% recorded is affected by coral disease and 50% is healthy. Heliofungia is the only genera of Fungiidae that is not affected by coral disease in all observation stations on Pramuka Island. Coral disease that identified has attack the Fungiidae are Yellow Band Disease, bleaching (stripes, spots, patches dan full), Sediment Damage, combination between Sediment Damage and Yellow Band Disease, and Enlarge Structure. Yellow Band Disease are the one that most appear, which is represent 67,69% of the total coral disease in the Fungiidae with the value of disease abundance is 0,37 individu/m2.